Evaluation Type of Fish on Nutritional and Sensory Properties of Fish-Flavoured-Spicy-Tamarind Cube - Binti Hanaffi, Nurlysa Affina (Enhanced Knowledge in Sciences and Technology, 2022)
Spicy tamarind is a common dish for Malaysian and is suitable to cook with any type of fish. Besides, seasoning cubes become more popular in the community as the fastest way of cooking. However, marine fish and freshwater fish has characteristics that could influence the nutrition and sensory properties of spicy tamarind cube. The aim of this study is to formulate fish-flavoured-spicy-tamarind cubes with different types of fish powders. Moreover, it also analyses the nutritional contents by their ash content, protein content, total fat content and minerals content. Besides, a sensory evaluation was conducted to determine the influence of fish powders on the sensory properties of the cube by evaluating its taste, aroma, texture (thickness of gravy) and overall acceptance. The results showed the range of ash content for all samples between 12.5% to 12.6% with sample FT and FC having the highest ash contents (12.6%). Besides, the protein content of the cubes showed a range of 9.4% to 9.5% and sample FT has the highest content of protein (9.5%). Moreover, the fat content of the cubes exhibited a significant difference with the sample FT and sample FC obtained the highest content of total fat (17.3%) and the lowest fat content was obtained by sample FA. Mineral detection showed the cubes consisted of potassium (K), iron (Fe), manganese (Mn), magnesium (Mg), sodium (Na), zinc (Zn), copper (Cu), tin (Tn), chlorine (Cl), calcium (Ca), phosphorus (P) and arsenic (Ar). In addition, the sensory evaluation results showed that sample FT was preferred in terms of its taste and texture (thickness of gravy) Meanwhile, sample FT and FC were also more accepted by panelists. In conclusion, freshwater fish managed to influence more the spicy-tamarind cube in terms of nutritional contents and sensory properties than marine fish as a previous study stated before.